CONCEPTUAL SYNTHESIS OF ENVIRONMENTAL SUSTAINABILITY IN TOURISM VILLAGES: SOCIOECOLOGICAL PERSPECTIVE (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
This study aims to conceptually synthesize environmental sustainability in tourism villages through a social-ecological systems approach based on an integrative literature review. The study is motivated by the dominance of social, economic, and governance dimensions in tourism village literature, while the integration of measurable environmental indicators—such as ecological resilience, land-use change, and carbon footprint—remains limited and fragmented. The research employs an integrative review design, analyzing 17 Scopus-indexed international journal articles relevant to sustainable tourism village development. Data were examined through variable extraction, thematic coding, and conceptual synthesis to identify theoretical evolution, integrative gaps, and multidimensional relational patterns among sustainability determinants. The findings indicate that although the literature has evolved in a multidimensional direction, it has not yet formed an integrated social-ecological systems model that positions environmental sustainability as the primary outcome. Measurable environmental indicators tend to be analyzed partially and have not been systematically linked to social, cultural, governance, and technological variables. This study concludes that an integrative conceptual framework is required to connect these determinants within a coherent analytical system. The primary contribution of this research lies in repositioning environmental sustainability as the core dimension of tourism village development and in providing a conceptual foundation for future empirical model development.